The impact of COVID-19 pandemic on food habits and neophobia in children in the framework of the family context and parents’ behaviors: A study in an Italian central region - Di Nucci, Annalisa; Scognamiglio, Umberto; Grant, Federica; Rossi, Laura (Frontiers in Nutrition, 2022)
Objective This paper aims to evaluate whether changes in lifestyle and eating habits resulting from the Covid-19 emergency have influenced the post-pandemic level of food neophobia and in children living in an Italian central region. Methods A sample of 99 children took part in a retrospective assessment carried out with a self-administrated questionnaire. Pre and post-pandemic evaluation of eating habits, physical activity, and lifestyle indicators was carried out. Food neophobia was evaluated following the Child Food Neophobia Scale (CFNS). Descriptive statistics were produced. A contingency analysis was performed to check associations between variables. Results For a large part of the sample (97%) the selective food refusal did not change during the pandemic period. About 70% of participants did not change their eating habits, with some subgroups reporting an increase in the consumption of fruits (22.2%), vegetables (19.2%), and legumes (21.2%). Relevantly the impact of the pandemic on the sedentary attitude passed from 25.3 to 70.7%. Neophobia was not associated with ponderal status (p-value 0.5). However, in normal-weight children, a high prevalence of intermediate-level neophobia (78.4%) was found. 39.4% of the studied children were involved in meal preparation during social isolation, with an increase in the proportion of children that shared all meals with their family (32.3% vs. 78.8%). Non-coercive parent behaviors in reaction to food refusal were associated with low levels of neophobia (p-value < 0.05). Discussion In this sample, for the effect of parents’ attitudes, the pandemic positively affected children’s food habits and, consequently, the level of neophobia after the social restrictions. The main implication of the study is the importance of capitalizing on the period of restrictions in order to involve children in meal sharing and food preparation.